Creating a Framework to Strengthen Cryptographic Security for Group Communication by Distributing Processed Keys - Bilas Haldar, Rohit Sinha, Pranam Paul (Mathematical Statistician and Engineering Applications, 2022)
In recent years the amount of secure transactions taking place over the internet has increased exponentially. The security of these transactions depends on the strength of the encryption and decryption techniques, and what lies at the heart of these techniques is sharing keys in a secure fashion. The primary goal of key exchange methods is to provide inherit security to the techniques and not depends on the security of the communication channels. In this work, we propose novel methods for generating keys for multi-party communication using the nth order of Quasi Group of numbers with arrangement and rearrangement. After extensive experimentation it was found that the proposed method have improved performance in comparison to benchmark tests in terms of time complexity and better security against standard attacks.